Extraction efficiency study of dysprosium and neodymium from acetic leaching solution of xenotime by Di-(2-ethylhexyl) phosphoric acid - Khaironie Mohamed Takip,; Noorashikin Md Saleh,; Roshasnorlyza Hazan,; Abdullah Amru Indera Luthfi, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The increasing importance of rare earth elements (REEs) in advanced technologies has prompted extensive research on their extraction, notably neodymium (Nd) and dysprosium (Dy), critical components for neo-magnet production. Researchers are actively exploring Nd and Dy recovery from both primary and secondary REE sources, often employing solvent extraction post-acid leaching for effective separation. In this context, a study focused on extracting Nd and Dy from local xenotime minerals utilizing acetic acid (CH3COOH) as the leaching solution and Di-(2-ethylhexyl) phosphoric acid (D2EHPA) in kerosene at a 30% concentration as the organic solvent. Energy Dispersive X-Ray Fluorescence (ED-XRF) analysis gauged Nd and Dy concentrations pre and post-extraction. The study identified optimal conditions, showing peak extraction efficiency: 99.4% for Nd and 99.3% for Dy, achieved using a 1M leaching solution concentration and a 1:1 aqueous-to-organic (A/O) phase volume ratio. The extraction process demonstrated highest efficacy at 30 °C within a 20-min timeframe. Consequently, the investigation highlights the potential of acetic acid as a xenotime leaching medium for Nd and Dy extraction with D2EHPA. Therefore, this study proves that CH3COOH is potentially be used as the leaching media of xenotime for the extraction of Nd and Dy with D2EHPA.